Microstructural characterization, driving mechanisms, and improvement strategies for interlayer bond strength of additive-manufactured cementitious composites: A review. (December 2022) - Danish, Aamar; Khurshid, Kiran; Mosaberpanah, Mohammad Ali; Ozbakkaloglu, Togay; Salim, Muhammad Usama
Abstract: 3D printed cementitious composites (3DPCC) are one of the contemporary digitization and fabrication techniques being adopted by the construction industry. Improving interlayer bond strength (IBS) is one of the most significant barriers to commercializing 3DPCC. This article focuses on the characterization of interlayer bond mechanism via microstructural characterization techniques such as scanning electron microscopy, computed tomography imaging, and mercury intrusion porosimetry. Moreover, different driving mechanisms that result in poor IBS of 3DPCC are critically analyzed, including thixotropic behavior, surface moisture content, mix design, surface roughness, time gap, nozzle standoff distance, and curing regime. Finally, this article thoroughly reviews mitigation strategies (such as mechanical interlocking and chemical bonding agent) to determine the best appropriate strategy for enhancing the IBS of 3DPCC. The results reveal that the poor IBS of 3DPCC is due to the formation of voids between the layers, which is caused primarily by a loss of surface moisture content and thixotropic behavior. However, because of its complex dependence on various parameters, the precise cause of weak interfacial properties is still unknown. With the use of a chemical bonding agent and mechanical interlocking mechanisms, the IBS of 3DPCC can be increased by 20–30% and 50–60%, respectively. The long-term performance of mitigation strategies, on the other hand, has not been thoroughly investigated. This article will help researchers understand the mechanism underlying 3DPCC's poor interfacial properties and develop new or improved enhancement strategies to promote 3DPCC preparation in the construction industry.